Placenta accreta spectrum disorders in the first trimester: a systematic review. (18th August 2022) - Guzmán López, Julieth Alexandra; Gutiérrez Sánchez, Luz Ángela; Pinilla-Monsalve, Gabriel David; Timor-Tritsch, Ilan E.
Abstract: Placenta accreta spectrum (PAS) disorders involve an abnormality in the implantation of the placenta, being rarely diagnosed in the first trimester. To conduct a systematic review of the risk factors, clinical and imaging features, and outcomes of histopathologically confirmed cases of PAS disorders in the first trimester of pregnancy. Different databases including PubMed, MEDLINE Complete, Scopus, Web of Science, EMBASE, SciELO, LILACS, and Ovid were reviewed up to November 2018. 55 patients with a definitive histopathological diagnosis were reported. About 18 had a history of prior curettage and 47 of previous caesarean deliveries (CD). About 74.54% presented with miscarriage and ultrasound signs of caesarean scar pregnancy (CSP) were reported in 22.49%. Temporal sequence of diagnostic studies could be determined in 52 women, and, among these, PAS disorders were defined through imaging techniques in 11 (21.15%) while surgical findings unveiled them in 15 (28.84%). Nonetheless, in half of the cases, the diagnosis was concluded only on histopathological samples. PAS disorders in the first trimester of pregnancy are rarely diagnosed through imaging techniques and lead to hysterectomy in most cases. Ultrasound training to detect PAS disorders in women with risk factors is crucial for early diagnosis and prevention of adverse outcomes.